2011
DOI: 10.1007/s10847-011-9994-6
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic studies on the inclusion interaction of p-sulfonatocalix[6]arene with vitamin B6

Abstract: The formation of the inclusion complex of p-sulfonatocalix[6]arene (SCX6) with different forms of vitamin B 6 (VB 6 ) was studied by using fluorescence spectroscopy. VB 6 can exist in one of three forms (the acidic form, neutral zwitterionic form and basic form) depending on pH. The fluorescence intensities of acidic and basic forms of VB 6 remarkably decreased in presence of SCX6. SCX6 preferred to form 1:1 inclusion complexes with acidic and basic forms of VB 6 but hardly form inclusion complex with neutral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Such research provides useful information for future design of macrocyclic molecules in the drug delivery application. 177 To achieve targeted drug delivery to minimize the side effect brought by nonspecific drug delivery, a folic acid−calix [4]arene conjugate was prepared ( Figure 10a). 178 Folic acid is known to serve as an efficient cancer cell targeting ligand, capable of binding to the folic acid receptor that is usually overexpressed in most cancer cells.…”
Section: Drug Deliverymentioning
confidence: 99%
“…Such research provides useful information for future design of macrocyclic molecules in the drug delivery application. 177 To achieve targeted drug delivery to minimize the side effect brought by nonspecific drug delivery, a folic acid−calix [4]arene conjugate was prepared ( Figure 10a). 178 Folic acid is known to serve as an efficient cancer cell targeting ligand, capable of binding to the folic acid receptor that is usually overexpressed in most cancer cells.…”
Section: Drug Deliverymentioning
confidence: 99%
“…Later, complexation studies of this vitamin were extended to include another CA derivative para ‐( para ‐sulfonated benzeneazo)calix[6]arene 138 . Besides, complexation properties of 125 toward another vitamin, B 6 , at different pH has been studied by Song et al…”
Section: Inclusion Complexes Of Aminocalix[n]arenesmentioning
confidence: 99%
“…Later, complexation studies of this vitamin were extended to include another CA derivative para-(para-sulfonated benzeneazo)calix [6]arene 138. 101 Besides, complexation properties of 125 toward another vitamin, B 6 , at different pH has been studied by Song et al 102 Complexes of norfloxacin, a synthetic antibacterial fluoroquinolone agent of the third generation, with 123 103 and 139 at pH 5, 105 as well as of lomefloxacin with 123 106 were investigated. Recent study regarding inclusion of norfloxacin into cavity of 126 published by another research group can also be found.…”
Section: Reviewmentioning
confidence: 99%
“…The size, polarity and other properties of the large cavity can be further modified by functionalization, which enables calixarenes to encapsulate cations, anions and neutral molecules. [4][5][6] The calixarene complexes thus formed play significant roles in environmental chemistry, co-ordination chemistry, nanoscience, biological sciences [7][8][9][10][11] etc. They also play an important role in drug development because of their ability to form inclusion complexes with neutral as well as ionic drug molecules.…”
Section: Introductionmentioning
confidence: 99%